Огляд захисних покриттів наночасток для біоінженерії та медицини - Чухно, Д. А. (ХНУРЕ, 2021)
The purpose of this paper is the analysis of magnetic nanoparticles with a modified by polysaccharide surface and the study of their properties. The process of applying a shell of glucose to magnetic nanoparticles was carried out by two methods (from the solution and by hydrothermal technology). The synthesized by hydrothermal method magnetic nanoparticles with a glucose shell were also analyzed. The analysis of the infrared spectra of the modified magnetic nanoparticles confirmed the presence of bands characteristic of hydrocarbons. The magnetic characteristics of the considered nanoparticles differ significantly, which is, to all appearance, because of the different conditions of the magnet oxidation process.
Keywords: наночастка; біоінженерія